Transition Structure Between Coaxial Cable and Dielectric Rod Waveguide in Microwave Frequency - Li, Yin; Zhou, Shi-Yan; Wong, Sai-Wai; Lin, Jing-Yu (Frontiers in Physics, 2021)
The dielectric waveguide in THz and millimeter circuit is widely researched. However, it is rarely researched in microwave frequency. In this paper, a dielectric rod waveguide (DRW) is proposed with low transmission loss in microwave frequency. For the purpose of impedance matching, a transition section comprised of the metal coated dielectric cavity and dielectric horn is presented to match the impedance between the coaxial cable and the dielectric rod waveguide. Finally, the dielectric rod waveguide and the transition section have been fabricated for experimental verification. The simulation and measurement results show an effective conversion between the coaxial cable and the dielectric rod waveguide.